Pemberian Creep Feed dengan Sumber Protein Berbeda terhadap Performa, Karkas, dan Kualitas Daging Domba Dorper: Effect of Creep Feed with Different Protein Sources on the Performance, Carcass, and Meat Quality of Dorper Sheep - Rangkuti, Farhan Ananda Rangkuti; Astuti, Dewi Apri; f, Dilla Mareistia; Tarigan, Andi (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2024)
The objective of this study is to evaluate the effectiveness of creep feed containing Indigofera and Black Soldier Fly (BSF) maggot meal and Indigofera on the performance and meat quality of Dorper lambs. The study involved 21 male lambs aged 3 months with an average weight of 20.03 ± 1.71 kg. A Completely Randomized Design (CRD) with 3 treatments and 7 replications was used, namely PM = Martabe feed, P1 = Indigofera creep feed, and P2 = BSF maggot creep feed. Parameters observed included performance, carcass characteristics, physical meat quality, nutrient composition, and fatty acid profile of Dorper lamb meat. Data were analyzed using Analysis of Variance (ANOVA), and significant differences were further analyzed using Duncan's test. The results showed that P2 significantly increased (p<0.05) consumption, daily weight gain, and carcass percentage compared to the other treatments. Although P1 did not show a significant difference in performance compared to the other treatments, it significantly affected (p<0.05) the protein content and improved the fatty acid profile of the meat. In conclusion, PM showed lower FCR and higher carcass percentage. P1 increased crude protein content of the meat, although it did not significantly affect physical meat quality. P2 improved ADG and carcass percentage of Dorper lambs compared to P1. Key words: creep feed, dorper sheep, quality meat, protein source